PROBLEMATIKA PENDIDIKAN ISLAM DI TIGA NEGARA INDONESIA,MALAYSIA DAN SINGAPURA - Badrul qomar; Aprima; Arifuddin Jalil; Ahsan Hakim (As-Sulthan Journal of Education, 2026)
Islamic education in Southeast Asia—specifically in Indonesia, Malaysia, and Singapore—faces unique, multidimensional challenges despite sharing common historical and cultural roots. This article analyzes the key issues facing Islamic education in these three countries, focusing on curriculum, state policy, the dualism of education systems, and the pressures of modernity. The study employs a comparative literature review using a descriptive-qualitative approach. Findings indicate that challenges in Indonesia center on the integration of religious and secular knowledge and disparities in institutional quality. Malaysia faces polarization between religious and national schools, exacerbated by ethnic-political interests, while Singapore grapples with identity and adaptation challenges within a strictly secular state framework. The study concludes by recommending integrative curriculum reforms and contextual policies that engage all stakeholders. Islamic education is a system rooted in Islamic values ​​derived from the Qur’an and Hadith. In practice across various nations, it confronts multidimensional challenges ranging from curriculum issues and educator quality to the impacts of globalization. This research focuses on identifying cross-national challenges in Islamic education and seeking applicable solutions through a qualitative literature review. Findings reveal that primary issues include the dualism of education systems, limitations in human resources and facilities, and the challenges posed by modernization and globalization. Islamic education serves as a cornerstone for character building among Muslims globally; however, the challenges faced vary by country, influenced by political, social, and cultural factors as well as levels of economic development. Consequently, this study comprehensively examines the various issues facing Islamic education in both Muslim-majority and Muslim-minority nations.